The catalytic core of Leishmania donovani RECQ helicase unwinds a wide spectrum of DNA substrates and is stimulated by replication protein A. (16th August 2021) - Shikha, Kumari; Sriram Bharath, Gugulothu; Mukhopadhyay, Swagata; Chakraborty, Mayukh; Ghosh, Susmita; Khatun, Suparna; De, Debajyoti; Gupta, Amar Nath; Ganguly, Agneyo
Abstract : RecQ helicases are superfamily 2 (SF2) DNA helicases that unwind a wide spectrum of complex DNA structures in a 3′ to 5′ direction and are involved in maintaining genome stability. RecQ helicases from protozoan parasites have gained significant interest in recent times because of their involvement in cellular DNA repair pathways, making them important targets for drug development. In this study, we report biophysical and biochemical characterization of the catalytic core of a RecQ helicase from hemoflagellate protozoan parasite Leishmania donovani . Among the two putative RecQ helicases identified in L . donovani, we cloned, overexpressed and purified the catalytic core of LdRECQb. The catalytic core was found to be very efficient in unwinding a wide variety of DNA substrates like forked duplex, 3′ tailed duplex and Holliday junction DNA. Interestingly, the helicase core also unwound blunt duplex with slightly less efficiency. The enzyme exhibited high level of DNA‐stimulated ATPase activity with preferential stimulation by forked duplex, Holliday junction and 3′ tailed duplex. Walker A motif lysine mutation severely affected the ATPase activity and significantly affected unwinding activity. Like many other RecQ helicases, L . donovani RECQb also possesses strand annealing activity. Unwinding of longer DNA substrates by LdRECQb catalytic core was found to be stimulated in the presence of replication protein A (LdRPA‐1) from L . donovani . Detailed biochemical characterization and comparison of kinetic parameters indicate that L. donovani RECQb shares considerable functional similarity with human Bloom syndrome helicase. Abstract : Visceral leishmaniasis is a fatal parasitic disease caused by the protozoan Leishmania donovani . RecQ helicases, which are highly conserved DNA helicases with a role in genome maintenance, are attractive targets for the development of antileishmanial drugs. Here, Agneyo Ganguly and colleagues characterised the catalytic core of one of two putative RecQ helicases in L. donovani, RECQb. The catalytic core was found to be able to efficiently unwind a wide variety of DNA substrates and mutation of a conserved lysine residue severely affected its unwinding activity. L. donovani RECQb was found to share considerable functional similarity with the human RecQ helicase implicated in Bloom syndrome.